Exhaled nitric oxide is not increased in pulmonary sarcoidosis - Cameli, Paolo; Barbagli, Elena; Rottoli, Paola (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
BACKGROUND: Fractional exhaled nitric oxide (FeNO) is a non-invasive biomarker of airway inflammation and nitrosative stress. Previous studies have suggested a possible role of FeNO in the management of patients with pulmonary sarcoidosis, but published data are discordant. OBJECTIVES: To assess the clinical usefulness of FeNO and alveolar concentration of NO (CalvNO) in sarcoidosis. METHODS: We measured FeNO50-100-150 and CalvNO in 31 patients with pulmonary sarcoidosis, 32 patients affected by idiopathic pulmonary fibrosis (IPF) and 30 healthy controls. RESULTS: Sarcoidosis group reported FeNO50-100-150 and CalvNO levels comparable to healthy controls, while IPF patients showed significantly higher values of FeNO50-100-150 and CalvNO than sarcoidosis (all p<0.05) and controls groups (all p<0.05). CONCLUSION: Exhaled nitric oxide is not a useful biomarker in the management of patients affected by pulmonary sarcoidosis.